Evaluasi Program One Day One Hadis Five Ayat Menggunakan Model Empowerment Evaluation di Pondok Pesantren Al Aqobah 4 Jombang - Muhamad Iqbal Wibisono; Suwadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to evaluate the effectiveness of the One Day One Hadith Five Verses program at Pondok Pesantren Al Aqobah 4 Jombang using the Empowerment Evaluation model. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation, and analyzed using thematic analysis with source and method triangulation. The findings indicate that the implementation of Empowerment Evaluation enhanced students’ participation, consistency in memorization activities, and the reflective capacity of both students and teachers in independently improving the program. Moreover, the participatory evaluation process fostered a strong sense of ownership and supported the development of a sustainable learning culture within the pesantren. This study contributes to the limited body of research on empowerment-based evaluation models in traditional Islamic boarding school contexts.